Edukasi Hasrat: Pendidikan di tengah Wacana Sekularisme dan Kebangsaan - Wilar, Abraham Silo (Theologia in Loco, 2022)
This study explores the traces of the desire for education historically and phenomenologically in Indonesia amid secularism and nationalism discourse. Several questions can be asked regarding the portrait of education amid the crush of secularism and nationalism. For example, what was the picture of the world of education and humans (as well as society) who were in the crush of secularism and nationalism? To address this question, I focus on the scope of locality, religious primordialism, and corruption as the primary problem. These three sections are reviewed to show the role of the desire for education in forming secularism and nationalism. Decentralization is a critical part of exploring the influence of locality in the formation of secularism and nationalism. Narratives of religious authorities show how religious primordialism affects the formation of secularism and nationalism.; on corruption, we are dealing with a systemic culture of corruption in both regional and central governments. Based on the three factors, I would like to highlight the portrait of education at that time and its role. From here, I move on to offer education on the desire that I borrowed from Timothy Schroeder to talk about motivation, enjoyment, and recognition that can shake and build human character. From this, I argue that education on desire is vital to manage human beings from the desire for hatred (religious), the desire to dominate, and the desire for political-economic satisfaction.